2012
DOI: 10.1002/hed.21975
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges facing biomarker development for personalized head and neck cancer treatment

Abstract: Head and neck oncologists have traditionally relied upon clinical tumor features and patient characteristics to guide care of individual patients. As surgical, radiotherapeutic, and systemic treatments have evolved to become more anatomically precise and mechanistically specific, the opportunity for improved cure and functional patient recovery has never been more promising for this historically debilitating cancer. However, personalized treatment must be accompanied by sophisticated patient selection to triag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 198 publications
(203 reference statements)
0
23
0
Order By: Relevance
“…Importantly, although the ML phenotype has been consistently associated with poor outcome, tumors displaying an epithelial‐like (EL) phenotype show widely diverse clinical behavior. Supporting this argument, genome‐wide association studies and gene expression analyses have identified distinct tumor subtypes, apart from ML tumors, which maintain EL features . The identification of specific markers able to stratify tumors sharing an EL phenotype would be helpful in identifying patients with a high risk of recurrence …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, although the ML phenotype has been consistently associated with poor outcome, tumors displaying an epithelial‐like (EL) phenotype show widely diverse clinical behavior. Supporting this argument, genome‐wide association studies and gene expression analyses have identified distinct tumor subtypes, apart from ML tumors, which maintain EL features . The identification of specific markers able to stratify tumors sharing an EL phenotype would be helpful in identifying patients with a high risk of recurrence …”
Section: Introductionmentioning
confidence: 99%
“…This represents an important facet and usage for PDXs, especially for cancers such as head and neck squamous cell carcinoma (HNSCC) where no currently validated predictive biomarkers exist. [8]…”
Section: Introductionmentioning
confidence: 99%
“…Every year Ͼ42,000 cases of oral, laryngeal, and pharyngeal cancer are diagnosed and Ͼ12,000 individuals die of the disease (3). The diagnosis and treatment of head and neck cancer presents several unique challenges.…”
mentioning
confidence: 99%